2020
DOI: 10.1021/acs.organomet.0c00010
|View full text |Cite
|
Sign up to set email alerts
|

Transmetalation as Key Step in the Diastereo- and Enantioselective Synergistic Cu/Pd-Catalyzed Allylboration of Alkynes with Racemic Allylic Carbonates

Abstract: Cu/Pd-catalyzed alkyne allylboration with racemic allylic carbonates proceeds with total inversion of configuration. Preliminary studies show that this synergistic catalysis can be used to perform a dynamic asymmetric allylic alkenylation that provides enantioenriched carboboration products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 60 publications
(32 reference statements)
0
15
0
Order By: Relevance
“…Notable contributions from Gong and Fu, as well as Fañanás-Mastral have illustrated methods utilizing alkynes as π-acceptors with allylic or propargylic alcohol derivatives (Scheme a), generating the boryl-functionalized skipped diene ( 114 ) or vinylallene ( 115 ) products. Fañanás-Mastral also examined the nature of the transmetalation by employing substrate 112c (Scheme b) . Complete inversion was observed indicating the organocopper had acted as a “hard” nucleophile via transmetalation and reductive elimination, instead of an outer-sphere process.…”
Section: Allylation/propargylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Notable contributions from Gong and Fu, as well as Fañanás-Mastral have illustrated methods utilizing alkynes as π-acceptors with allylic or propargylic alcohol derivatives (Scheme a), generating the boryl-functionalized skipped diene ( 114 ) or vinylallene ( 115 ) products. Fañanás-Mastral also examined the nature of the transmetalation by employing substrate 112c (Scheme b) . Complete inversion was observed indicating the organocopper had acted as a “hard” nucleophile via transmetalation and reductive elimination, instead of an outer-sphere process.…”
Section: Allylation/propargylationmentioning
confidence: 99%
“…Fanãnaś-Mastral also examined the nature of the transmetalation by employing substrate 112c (Scheme 30b). 93 Complete inversion was observed indicating the organocopper had acted as a "hard" nucleophile via transmetalation and reductive elimination, instead of an outer-sphere process.…”
Section: Allylation/propargylationmentioning
confidence: 99%
“…Very recently, Fañanás-Mastral’s group has demonstrated that Cu-alkenylboranes, generated in situ from alkynes, can also be used as nonstabilized carbon nucleophiles in allylic substitutions with cyclic allylic carbonates, although the enantioselectivities were only moderate (up to 54% ee ). 432 …”
Section: Asymmetric Allylic Substitutionmentioning
confidence: 99%
“…Very recently, Fanãnaś-Mastral's group has demonstrated that Cu-alkenylboranes, generated in situ from alkynes, can also be used as nonstabilized carbon nucleophiles in allylic substitutions with cyclic allylic carbonates, although the enantioselectivities were only moderate (up to 54% ee). 432 Metalated 2-methyl-substituted 433 and related 2-substituted 434 pyridines were also successfully used as nucleophiles in this transformation by Trost and co-workers (Scheme 142). It was found that precomplexation of the pyridine unit to BF 3 • Et 2 O was necessary.…”
Section: Other C-nucleophilesmentioning
confidence: 99%
“…Recently, they have developed a diastereo-and enantioselective bimetallic Cu/Pd-catalyzed allylboration of terminal alkynes with racemic allyl carbonates and B 2 pin 2 (Scheme 23b). [140] The in situ generated β-borylalkenyl-copper species acts as a "hard" nucleophile and participate in the Pd-catalyzed allylation step with racemic allylic substrate to cause total inversion of configuration. Fu Group reported bimetallic Cu/Pd-catalyzed boryldifluoroallylation of alkynes to access gem-difluorodiene scaffolds under mild conditions with high regio-and stereoselectivity (Scheme 23c).…”
Section: Carboboration Of Alkynesmentioning
confidence: 99%